Contemporary developments in Indonesian Islam : explaining the "conservative turn" - Van Bruinessen, Martin (Institute of Southeast Asian Studies, 2013)
Once celebrated in the Western media as a shining example of a "liberal" and "tolerant" Islam, Indonesia since the end of the Soeharto regime (May 1998) has witnessed a variety of developments that bespeak a conservative turn in the country's Muslim politics. In this collection of original essays, the editor - a senior Western scholar of Indonesian Islam - and four leading Indonesian Muslim scholars explore and explain these developments. Each chapter examines trends from a strategic institutional perch: the Council of Indonesian Muslim scholars, the reformist Muhammadiyah, South Sulawesi's Committee for the Implementation of Islamic Shari'a, and radical Islamism in Solo. These essays shed a bright light on what Indonesian Muslim politics was - and where it seems to be going.